2011
DOI: 10.4103/0970-9185.83681
|View full text |Cite
|
Sign up to set email alerts
|

Influence of music on operation theatre staff

Abstract: Background and Objective:The purpose of the study was to evaluate the perception of influence of music among surgeons, anesthesiologist and nurses in our hospital as well as to critically evaluate whether music can be used as an aid in improving the work efficiency of medical personnel in the operation theatre (OT).Materials and Methods:A prospective, questionnaire-based cross-sectional study was conducted. A total of 100 randomly selected subjects were interviewed, which included 44 surgeons, 25 anesthesiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…As for the surgeon, music seems to have several advantages over performance and efficiency by improving accuracy, concentration and speed during the performance of tasks. Endurance also seems to be improved by the effects of music on muscle recruitment [ 47 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the surgeon, music seems to have several advantages over performance and efficiency by improving accuracy, concentration and speed during the performance of tasks. Endurance also seems to be improved by the effects of music on muscle recruitment [ 47 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the performance report showed that there was still some “irrelevant chatting” or “loud music”. This indicates that procedures were performed in the familiar and natural way [ 26 , 52 , 53 ]. Quotes during the debriefings confirmed that there was often a very relaxed and good atmosphere in the OR.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that music can reduce autonomic reactivity and enhance performance. [13] George et al .,[14] also observed that music can aid in improving the work efficiency of medical personnel in the OR. Familiar and self-chosen music have favorable effect than the music which people didn’t like or were indifferent to.…”
Section: Discussionmentioning
confidence: 99%